ENGLISH PRONUNCIATION ERRORS BY SUNDANESE SPEAKERS - Dwi Warry Octaviana (UIBU, 2019)
The students’ first language (Sundanese) often interferes with English pronunciation. For example, the students get difficulties to distinguish in pronouncing certain sounds of vowels such as between /e/ in ‘beg’ and /æ/ in ‘bag’, /ei/ in ‘wait’ and /e/ in ‘wet’. Sometimes, the students will be able to identify specific problem sounds and sometimes they will not. Another challenge resulting from differences in the first language is the inability to hear certain English sounds that the students’ native language does not contain. Therefore, the study was aimed at finding out the main factors that cause the students’ English pronunciation errors and identifying the types of the students’ English pronunciation errors. In acquiring the data, the research used descriptive method. The data needed are gained through a sample consisting 10 of 32 students. The sample was randomly selected. The students were given ten items of questionnaire asking for their responses in line with the causes of their English pronunciation errors. Then, the students’ English pronunciation errors were found from the analysis of the reading material that had been read by the students. In relation to the data gained, the data findings showed that the main factors that caused the students’ English pronunciation errors were coming from internal factors (lack of practice, lack of self-confidence, and lack of exposure) and from the external factors (the differences in pronunciation between the students’ first language (Sundanese) and their target language (English) and the differences between what the correct pronunciation that should be pronounced and its writing actually). After the investigation, the types of English pronunciation errors made by the students in vowels sound were: long and short vowels, diphthongs, and triphthongs. It was caused by the inability to hear certain English sounds that the students’ native language does not contain.